2021
DOI: 10.24272/j.issn.2095-8137.2021.044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of intermuscular bone development in fish: a review

Abstract: Intermuscular bones (IBs) are slender linear bones embedded in muscle, which ossify from tendons through a process of intramembranous ossification, and only exist in basal teleosts. IBs are essential for fish swimming, but they present a choking risk during human consumption, especially in children, which can lead to commercial risks that have a negative impact on the aquaculture of these fish. In this review, we discuss the morphogenesis and functions of IBs, including their underlying molecular mechanisms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 93 publications
0
9
0
1
Order By: Relevance
“…Many signaling pathways are involved in bone regeneration, such as the Wnt/β-catenin pathway, BMP/Smad pathway, Hedgehog pathway, and Notch pathway ( Yan and Alman, 2009 ). The key signaling pathway involved in the IB developmental stages (S1–S4) includes cyclic adenosine monophosphate (cAMP), phosphatidylinositol 3′-kinase-Akt (PI3K-Akt), mitogen-activated protein kinase (MAPK), tumor necrosis factor (TNF) signaling, and vascular endothelial growth factor (VEGF) signaling ( Wan et al, 2016 ; Nie C.-H. et al, 2019 ; Li et al, 2021 ). P53 inhibits the expression of OSX (Sp7) to prevent bone development and osteoblast differentiation ( Sinha and Zhou, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many signaling pathways are involved in bone regeneration, such as the Wnt/β-catenin pathway, BMP/Smad pathway, Hedgehog pathway, and Notch pathway ( Yan and Alman, 2009 ). The key signaling pathway involved in the IB developmental stages (S1–S4) includes cyclic adenosine monophosphate (cAMP), phosphatidylinositol 3′-kinase-Akt (PI3K-Akt), mitogen-activated protein kinase (MAPK), tumor necrosis factor (TNF) signaling, and vascular endothelial growth factor (VEGF) signaling ( Wan et al, 2016 ; Nie C.-H. et al, 2019 ; Li et al, 2021 ). P53 inhibits the expression of OSX (Sp7) to prevent bone development and osteoblast differentiation ( Sinha and Zhou, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBs are small, hard-boned spicules located in the muscle tissue on both sides of the vertebrae; they mainly exist in the myosepta of lower teleosts ( Li et al, 2013 ; Nie C.-H. et al, 2019 ). IBs are difficult to remove, so they may be dangerous when consumed and are not conducive to the processing of aquatic products ( Li et al, 2021 ). Therefore, IBs have been recognized as a noteworthy feature in aquaculture breeding programs because of their negative effect on the edibleness and economic value of fishes ( Nie C. H. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermuscular bones form an integral part of the skeletal system in teleost fish. They are located in the myosepta on both sides of the vertebrae and considered to develop via intramembranous ossification of myoseptal tendons without undergoing a cartilaginous phase ( Li et al, 2021 ; Nie et al, 2019 ). In most teleost fish, there are three sets of intermuscular bones: epineurals, epicentrals and epipleurals, attaching ligamentously to neural, central and hemal arches or ribs, respectively ( Nie et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…p53 is also present in some newly discovered biological processes, such as ferroptosis (39,40). In terms of osteogenesis, several researchers have identified a negative regulatory effect of p53 on osteoblast differentiation, whereas some others suggested that mutations in p53 can increase osteoblast differentiation (41,42). The present study found that p53 was expressed in all MSCs tested and overexpression of p53 enhanced the potential of BMP9 induced osteogenic differentiation, while suppression of p53 decreased the expression level of early, intermediate, and late osteogenic markers, whereas p53 alone had no significant effect on MSCs differentiation in this study.…”
Section: Discussionmentioning
confidence: 99%